1991
DOI: 10.1152/ajpregu.1991.261.6.r1418
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability as a measure of autonomic function during weight change in humans

Abstract: Changes in autonomic function were studied during experimentally induced weight changes in seven subjects. A spectral analysis of heart rate variability (HRV) was used to evaluate autonomic activity during weight change. With a 10% increase in body weight above the usual or starting weight, there was a decline in parasympathetic power accompanied by a rise in mean heart rate. Heart rate declined during weight reduction, but the power of HRV did not change significantly. Because heart rate power at the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 2 publications
(3 reference statements)
5
79
0
2
Order By: Relevance
“…32,35 Our characterization of the muscarinic signaling system in atrial cardiomyocytes could explain certain clinical features seen in obese patients with hyperinsulinemia, such as hypertension, tachycardia or increased risk of sudden cardiac death. Previous clinical studies have found that a lower parasympathetic function was associated with increasing body fat, 11,36,37 and that parasympathetic withdrawal in obese patients was correlated with hyperinsulinemia. 19 Moreover, evidence converges on the conclusion that abnormal variations in plasma insulin levels elicit repeated Insulin effect on cardiac M 2 -muscarinic receptor and signaling A Pathak et al episodes of parasympathetic withdrawal.…”
Section: Discussionmentioning
confidence: 90%
“…32,35 Our characterization of the muscarinic signaling system in atrial cardiomyocytes could explain certain clinical features seen in obese patients with hyperinsulinemia, such as hypertension, tachycardia or increased risk of sudden cardiac death. Previous clinical studies have found that a lower parasympathetic function was associated with increasing body fat, 11,36,37 and that parasympathetic withdrawal in obese patients was correlated with hyperinsulinemia. 19 Moreover, evidence converges on the conclusion that abnormal variations in plasma insulin levels elicit repeated Insulin effect on cardiac M 2 -muscarinic receptor and signaling A Pathak et al episodes of parasympathetic withdrawal.…”
Section: Discussionmentioning
confidence: 90%
“…14 Lastly, autonomic disturbances are reported in the obese state 17,18 and with weight loss under controlled experimental conditions. 19 Thus, although mechanisms of cardiac repolarization change were not explored in the present study, autonomic mechanisms may in-part explain the observed QT and QTc interval reductions.…”
Section: Potential Mechanismmentioning
confidence: 81%
“…Perhaps more important are the observations of impaired heart rate variability, increased heart rate, cardiac output and peripheral vasodilation in overweight individuals that are apparently healthy, normotensive and normoglycemic. 18,28 This 'high-output, low-resistance' haemodynamic milieu will reasonably be expected to result in significantly lower central SBP compared with peripheral SBP (increased SBP amplification), and thereby potentially help explain the differential relationships between body size and central versus peripheral BP. 23,29 Further studies are needed to understand the relation between body size and central BP.…”
Section: Central Bp and Body Sizementioning
confidence: 99%